Regulation of nuclear DNA damage response by mitochondrial morphofunctional pathway. Issue 16 (18th August 2022) - Oanh, Nguyen Thi Kim; Lee, Ho-Soo; Kim, Yong-Hyun; Min, Sunwoo; Park, Yeon-Ji; Heo, June; Park, Yong-Yea; Lim, Won-Chung; Cho, Hyeseong
Abstract: Cells are constantly challenged by genotoxic stresses that can lead to genome instability. The integrity of the nuclear genome is preserved by the DNA damage response (DDR) and repair. Additionally, these stresses can induce mitochondria to transiently hyperfuse; however, it remains unclear whether canonical DDR is linked to these mitochondrial morphological changes. Here, we report that the abolition of mitochondrial fusion causes a substantial defect in the ATM-mediated DDR signaling. This deficiency is overcome by the restoration of mitochondria fusion. In cells with fragmented mitochondria, genotoxic stress-induced activation of JNK and its translocation to DNA lesion are lost. Importantly, the mitochondrial fusion machinery of MFN1/MFN2 associates with Sab (SH3BP5) and JNK, and these interactions are indispensable for the Sab-mediated activation of JNK and the ATM-mediated DDR signaling. Accordingly, the formation of BRCA1 and 53BP1 foci, as well as homology and end-joining repair are impaired in cells with fragmented mitochondria. Together, these data show that mitochondrial fusion-dependent JNK signaling is essential for the DDR, providing vital insight into the integration of nuclear and cytoplasmic stress signals.